Dilemmas in determinism the prevalence of human personality over the designed environment of Gawad Kalinga-Baseco - Perez, Angelito Rene R. (2014)
This research argues that designed environments can only influence user behavior to a certain extent, and that environment is ultimately shaped by the personality of its users, contrary to theories of architectural determinism. A case study of a community development model called Gawad Kalinga in Baseco, Manila was pursued in August 2011, where a contextualized personality tool based from the Myers-Briggs Type Indicator was administered to respondents, identifying linking psychological tendencies and subsequently linking these to their various responses toward space. The behavioral inclinations, which were documented in the findings, of the respondents towards space tend to support the argument that design cannot be imposed with outright determinism.

Findings showed the need for a holistic planning approach, with the city government linking public and private initiatives. Recommendations included urban renewal efforts addressing pedestrianization issues through street improvements, traffic decongestion, and security by design approaches.
Keywords: Housing -- Baseco, Manila; Gawad Kalinga (Baseco, Manila)